Cross-Border Banking in Regulated Markets: Is Financial Integration Desirable? - Andreas Haufler; Ian Wooton (Center for Economic Studies and ifo Institute (CESifo), 2016)
We set up a two-country, regional model of trade in financial services. Competitive firms in each country manufacture untraded consumer goods in an uncertain productive environment, borrowing funds from a bank in either the home or the foreign market. Duopolistic banks can choose their levels of monitoring of firms and thus the levels of risk-taking, where the risk of bank failure is partly borne by taxpayers in the banks' home countries. Moreover, each bank chooses the share of its lending allocated between domestic and foreign firms, but the bank's overall loan volume is fixed by a capital requirement set optimally in its home country. In this setting we consider two types of financial integration. A reduction in the transaction costs of cross-border banking reduces aggregate output and increases risk-taking, thus harming consumers and taxpayers in both countries. In contrast, a reduction in the costs of screening foreign firms is likely to be beneficial for banks, consumers, and taxpayers alike.
Keywords: F36; G18; H81; 330; cross-border banking; capital regulation; financial integration